Ethical aspects of health and wellbeing of young elite athletes conceptual and normative issues - Zurc, Joca (2020)
Sport and physical activities offer a sensitive environment where the values of humanity, human rights, empathy and fair play come to the fore. However, at the same time the competition nature of sport and the interest of winning at any cost represent a risks of harm, especially for young preadolescent athletes. Therefore, the need arises to identify the main ethical conceptual and normative issues of the top youth sport. Our critical review of possible risk factors and empirical findings of semi structured in-depth interviews with four top-level gymnastics’ coaches showed that achievements of children in sport are the result of multiple factors driven by the main force of the ethics of maximum behind. Gymnasts’ intrinsic motivation, pleasure to sport, persistent hard work, start at early age, and the role of parents are essential for success. However, the morality of the coach as a reflection of society values should be carefully considered in the future.
Sport i fizička aktivnost nude osjetljivo okruženje u kojemu se ističu vrijednosti čovječnosti, ljudskih prava, empatije i ferpleja. Međutim, istovremeno natjecateljska priroda sporta i interes za pobjeđivanje pod svaku cijenu predstavlja rizik štete, posebno za mlade predadolescentske atletičare. Stoga se javlja potreba za utvrđivanjem glavnih etičkih koncepcijskih i normativnih problema u vrhunskom sportu mladih. Naš kritički pregled mogućih faktora rizika i empirijskih pronalazaka u djelomično strukturiranim dubinskim intervjuima s četiri vrhunska trenera gimnastike pokazala su da su uspjesi djece u sportu rezultat višestrukih faktora poticanih glavnom silom etike maksimuma. Intrinzična motivacija gimnastičara, zadovoljstvo bavljenje sportom, ustrajni predan rad, rani početak i uloga roditelja ključni su za uspjeh. Međutim, moralnost trenera kao odražavatelja društvenih vrijednosti trebalo bi ubuduće pomno razmotriti.
Ein Kind gemäß den hohen ethischen Grundsätzen aufzuziehen ist das Ziel jeglicher Erziehung und Erwartung eines jeden Elternteils. Sport und körperliche Aktivitäten bieten ein sensibles Umfeld, in dem die Werte der Menschlichkeit, Menschenrechte, Empathie und des Fair Play in den Vordergrund rücken. Gleichzeitig stellen aber die Wettbewerbsnatur des Sports und das Interesse, um jeden Preis zu gewinnen, ein Schadensrisiko dar, namentlich für junge voradoleszente Sportler. Daher besteht die Notwendigkeit, die wichtigsten ethischen konzeptionellen und normativen Probleme des Spitzensports bei Jugendlichen zu identifizieren. Unsere kritische Überprüfung möglicher Risikofaktoren und der empirischen Befunde der halbstrukturierten Tiefeninterviews mit vier Spitzenturnen-Trainern zeigte, dass die Leistungen von Kindern im Sport das Ergebnis mehrerer Faktoren sind, die von der dahinter liegenden Hauptkraft der Ethik des Maximums getrieben werden. Die intrinsische Motivation der Turner, die Freude am Sport, die anhaltende harte Arbeit, der Start im frühen Alter und die Rolle der Eltern sind ausschlaggebend für den Erfolg. Die Moralität des Trainers als Spiegelbild gesellschaftlicher Werte sollte jedoch in Zukunft sorgfältig abgewogen werden.
Élever un enfant en accord avec des normes éthiques rigoureuses est l’objectif de toute éducation et de chaque parent. Le sport et les activités physiques offrent un environnement sensible où les valeurs humaines, les droits humains, l’empathie et le fair-play sont mis au premier plan. Cependant, la nature compétitive du sport et l’intérêt pour une victoire à n’importe quel prix présentent un risque de préjudice, spécialement pour les jeunes athlètes préadolescents. Ainsi émerge le besoin d’identifier les conceptions éthiques majeures et les problèmes normatifs dans le sport de haut niveau chez les jeunes. Notre examen critique des possibles facteurs à risques et les résultats empiriques des entretiens semi structurés et approfondis réalisés auprès de quatre entraîneurs de gymnastes de haut niveau ont montré que la réussite des enfants dans le sport est le résultat de multiples facteurs qui découlent de la principale force de l’éthique à conduire le sportif à son maximum. La motivation intrinsèque des gymnastes, la plaisir du sport, le travail assidu, les débuts à un âge précoce et le rôle des parents sont essentiels pour le succès. Cependant, la morale de l’entraîneur comme reflet des valeurs de la société devrait à l’avenir être considérée avec soin.
Bilješke uz tekst.
Bibliografske bilješke uz tekst.
Abstract ; Sažetak ; Zusammenfassung ; Résumé.
Keywords: Etika sporta -- Sport -- Razvoj talenta -- Djeca -- Sportska gimnastika